REFUTATION OF LAURA MULVEY'S 'MALE GAZE' THEORY IN FILM LITTLE WOMEN (2019) - Virgiena Salsabila; Lili Awaludin; Hasbi Assiddiqi (Saksama: Jurnal Sastra, 2022)
Film, along with other literary works such as books, poetry and theater, is one of the mediums used in the contemporary day to communicate messages to society. Greta Gerwig adapted the film Little Women (2019) from the novel Little Women (1868) by Louisa May Alcott. This film shows a breakthrough over the prejudice and discrimination towards women in 19th-century cinema. The subject of female gaze has received attention since, up to this point, women have frequently only been shown as passive narrative objects, or even as the principal sexual objects in movies. Analyzing by comparing Laura Mulvey's theory regarding female gaze and male gaze through the phenomena contained in the film Little Women, which narrates the lives of five young women during their adolescent years. The image of women in the film Little Women does not appear as an object but a subject, the characters in the film Little appears strong, ambitious and optimistic. Little Women proves that Mulvey's theory of the patriarchal world is neither permanent nor obligatory.